A Game-Theoretic and Multimodal Interaction Framework for Collaborative Robots in Smart Manufacturing - Dongdong Chu; Shulan Yu; Yuhang Ling; Yang Zhao; Jianhong Zhang (Decision Making: Applications in Management and Engineering, 2024)
Industrial assembly settings have encountered novel challenges following the integration of collaborative robots (cobots), particularly in maintaining a balance between effective human-robot interaction and operational efficiency. Interpreting and implementing complex human behaviours remains a significant difficulty, especially in conventional operations conducted under dynamic and unpredictable conditions. A critical requirement has emerged for the development of intelligent interfaces capable of autonomously regulating systems while facilitating seamless collaboration between human operators and robotic agents. This study focuses on a multimodal perception approach enhanced by game-theoretic optimisation, which has been shown to improve cobots’ responsiveness and strategic flexibility. Researchers have chosen this method due to its capacity to model interactive behaviours in variable environments. By integrating vision, auditory, and tactile sensing technologies, cobots are equipped to accurately interpret human communicative cues, even when operating with limited capabilities. The proposed framework utilises game theory to model the strategic and dynamic interactions between humans and robots, thereby addressing the dual challenges of task allocation and decision-making. This system supports optimal coordination and prompt conflict resolution, while enabling real-time behavioural adjustments based on utility-driven outcomes. Its efficacy has been validated through both simulated and practical implementations in industrial assembly scenarios, confirming its potential to enhance collaborative efficiency and safety while maintaining adaptability. Overall, this research presents a strategic design framework for cobot interaction that emphasises perceptual processing, contributing to substantial advancements in the evolution of intelligent manufacturing systems